Oleoylethanolamide Ameliorates Dextran Sulfate Sodium-Induced Colitis in Rats - Otagiri, Shinsuke; Ohnishi, Shunsuke; Ohara, Masatsugu; Fu, Qingjie; Yamamoto, Koji; Yamamoto, Keiko; Katsurada, Takehiko; Sakamoto, Naoya (Frontiers in Pharmacology, 2020)
Oleoylethanolamide (OEA) is an endogenous fatty acid ethanolamide known for its anti-inflammatory effects and its influence on gut microbiota composition; however, the effects of OEA in inflammatory bowel disease (IBD) remain unknown. During in vitro experiments, OEA downregulated the expression of tumor necrosis factor (TNF)-a and reduced phosphorylation of inhibitor of kappa (Ik) Ba induced by lipopolysaccharide in human embryonic kidney cells. Moreover, OEA downregulated the expression of interleukin (IL)-8 and IL-1b and inhibited the phosphorylation of IkBa and p65 induced by TNF-a in human enterocytes (Caco-2). The effect of OEA in reducing the expression of IL-8 was blocked by the peroxisome proliferator-activated receptor (PPAR)-a antagonist. During in vivo experiments on rats, colitis was induced by the oral administration of 8% dextran sulfate sodium from day 0 through day 5, and OEA (20 mg/kg) was intraperitoneally injected once a day from day 0 for 6 days. OEA administration significantly ameliorated the reduction in body weight, the increase in disease activity index score, and the shortening of colon length. In rectums, OEA administration reduced the infiltration of macrophages and neutrophils and tended to reduce the histological score and the expression of inflammatory cytokines. Administration of OEA produced significant improvement in a colitis model, possibly by inhibiting the nuclear factor kappa B signaling pathway through PPAR-a receptors. OEA could be a potential new treatment for IBD.